Cryoglobulinemic Glomerulonephritis: A Case Report - Nuntawan Piyaphanee (Siriraj Medical Journal, 2017)
Cryoglobulinemic glomerulonephritis (CG) is rare in children. We report a 13-year-old Thai boy who presented with acute nephrotic nephritis syndrome, arthralgia, and purpura. Renal pathology revealed membranoproliferative glomerulonephritis and CG. No secondary causes of CG were found. He responded well to 12 weeks of oral cyclophosphamide plus low dose prednisolone and azathioprine for maintenance. He was doing well at 31 weeks but long term follow up is required as chronic renal failure and neoplasia were reported.